Accounting for spellings: Ambisyllabic consonants in L2 German spelling discussions. Issue 1 (2nd January 2019) - Geist, Barbara; Kupetz, Maxi; Glaser, Karen
ABSTRACT: In primary-level German writing instruction, spelling discussions (German: Rechtschreibgespräche ) have become a well-established interactional method of teaching orthography, prompting the children to exchange their hypotheses about orthographic features of written words. Focusing on spellings of ambisyllabic consonants, this conversation-analytic paper reports about teacher-led and small-group spelling discussions of fourth-graders in a German school in Spain. As the data show, the students and the teacher approach and accomplish the task of accounting for the spellings of pre-selected words in various ways: by drawing on vowel quantity, by comparing phonetic minimal pairs, by applying morphologic extension, and by employing oral syllabifying as well as syllable scooping. The findings indicate that spelling discussions provide opportunities for teachers and students to negotiate their understanding of orthographic rules while displaying metalinguistic knowledge and practicing communicative skills. Illuminating how theoretic-didactic approaches to spelling instruction are put into practice in the classroom, the data reveal that the participants do not strictly adhere to one single approach, but creatively draw on various operations to account for a specific spelling. From these observations we derive insights for the training of (future) L1 and L2 German teachers.